当院救命センターにおけるヒヤリハット解析からみたノンテクニカルスキルの重要性 - 齊藤, 晃; 下松谷, 匠; 中村, 誠昌; 中村, 一郎; 長門, 優; 東口, 貴之; 西嶋, 道子; 丹後, 泰久; 塩見, 尚礼; 谷口, 正展; 張, 弘富 (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2018)
Our hospital is a core hospital with 540 beds and an emergency medical center, which is in the Kohoku area, Shiga prefecture. Our hospital’s center is operated by not only full-time staff but also staff who are working as part-timers. In order to reduce incidents in such a mixed team, it is important not only to brush-up on technical skills but also to improve non-technical skills. 当院は救命救急センターを擁して滋賀県湖北医療圏で三次救急を担当する540床の中核病院である。当院の救命センターのスタッフは専任ではなく兼任スタッフを含めて運用している。このような混合チームにおいてヒヤリハットを減少させるにはテクニカルスキルのブラッシュアップのみならずノンテクニカルスキルの向上が必須である。